Pengaruh Penggunaan Layanan Google Untuk Mendukung Prestasi Belajar Siswa Sekolah Menengah Kejuruan (SMK) di Kota Palembang - Imamulhakim Syahid Putra; Aminullah Imal Alfresi (Systemic: Information System and Informatics Journal, 2019)
This study aims to determine what factors influence learning achievement after using Google Search services, and how much influence Google services have in supporting the learning achievement of vocational middle school students, so that it can support the achievement of vocational middle school students. This study uses multiple regression analysis, the population in the study were all vocational high school students who had used Google.com or Google.co.id applications with a total sample of 202 students using random sampling technique. Data collection techniques with the distribution of Likert scale questionnaires, processing primary data using statistical tests and SPSS version 20 applications. Test requirements analysis using validity, reliability, and hypothesis testing. The questionnaire used in the study as a measure of the level of validity by referring to the table value, where the correlation value to be used to measure the validity of r count must be positive and greater. In this study n = 99 with a significance level of 5%, the r table is 0.1956. While testing the reliability of the entire system used in measuring the X3 variable produces a coefficient (cronbach's alpha) of 0.557. This reliability coefficient value if <0.60 can be said that the instrument used to measure the variable X3 is declared quite reliable. Then to test the hypothesis consists of t test and test f. Based on the F test obtained significant value (p value) is obtained as much as 0,000, when compared with 95% confidence level, with a value of = 0.05 (0.000 <0.05) on the basis of these comparisons, the statement on Hypothesis Ha can be accepted or in words other that the independent variables, namely information quality, user intensity, and learning resources simultaneously influence the dependent variable, namely learning achievement. The results of the research can later provide information and knowledge for students and the school and as a theoretical basis in supporting the learning of students in vocational high schools. Keywords: Google, Learning Achievement, SPSS, Vocational High School